Investigation of contrarian strategies in the China market. - Tan, Li Ling. (2009)
This study investigates the existence of contrarian profits in China stock markets when we buy losers and sell winners. The findings show that in the absence of transaction costs, short-term contrarian strategies do not generate significant profits, whereas significant intermediate and long-term contrarian profits exist. We carry out a two-stage regression to control for risks identified by the Fama and French three-factor model and establish that past returns are predictive of future returns. Our results are robust when using Fama and MacBeth regression. Taken together, our findings suggest that long-term contrarian profits exist in the China stock markets.